Aida Times Two: How Italian Veterans of Two Historic Aida Productions Shaped Argentina's Music History. (20th June 2016) - Cetrangolo, Aníbal Enrique
Abstract: Aida famously inaugurated the Teatro Colón in Buenos Aires in 1908, but the musical history of the city is also linked to two earlier productions of the piece: its debut in Cairo in 1871, and another legendary performance, in Rio de Janeiro in 1886. This article retraces the steps of five Italian musicians who played in the orchestras of the Cairo or Rio productions before moving to Buenos Aires, and thereby formed part of the vast Italian emigration to Argentina in the final decades of the nineteenth century. Once there, Pietro Melani, Tomaso Marenco, Giovanni Grazioso Panizza, Italo Casella and Ferruccio Cattelani radically transformed the concert life of the city through their musical activities, not least through their introduction of a wide range of orchestral and chamber music repertoire. By reconstructing their trajectories, I argue for a stronger focus on international networks in thinking about the history of Italian opera at this time and for a greater attention to the contributions of performers who would later fall into obscurity. In addition, I suggest that the insignificant attention given to such figures even in Argentinean narratives would seem to indicate the persistence of a historiography that plays down the contributions of European immigrants in the musical history of the city and the nation.